THE CULTURAL DIMENSIONS OF HOFSTEDE IN A SMALL ADVERTISING COMPANY: THE CULTURAL DIMENSIONS OF HOFSTEDE IN A SMALL ADVERTISING COMPANY - Callefi, Jéssica Syrio; Bacellar, Luiz Fernando Strauss; Lourenço, Caio Marcelo; Santos, Fernando César Almada (Brazilian Journal of Production Engineering, 2020)
Micro and small companies represent a significant part of the jobs and income generated in Brazilian society. According to Sebrae (2016), they hired 9 million workers, 60% more than medium and large companies. Realizing the challenges of these companies and presenting solutions contributes to the development of new jobs and, consequently, to the country’s economic growth. There is a strong influence of organizational culture on the development and maintenance of small businesses. Thus, this article aims to identify the cultural dimensions of a small company with good performance in the area of ​​digital marketing. Hofstede’s cultural dimensions were used for the bibliographic review, focusing on how Brazilian companies fit into these dimensions. Thus, the analyzed company was classified among the dimensions presented by Hofstede to understand its characteristics. As a result, the influence of organizational culture on the company’s development steps is observed, which had not been mapped by the analyzed company.